The impact of manipulating personal standards on eating attitudes and behaviour - Shafran, R; Lee, M; Payne, E; Fairburn, C (2006)
The relationship between perfectionism and eating disorders is well established and is of theoretical interest. This study used an experimental design to test the hypothesis that manipulating personal standards, a central feature of perfectionism, would influence eating attitudes and behaviour. Forty-one healthy women were randomly assigned either to a high personal standards condition ( n = 18) or to a low personal standards condition for 24 h ( n = 23). Measures of personal standards, perfectionism, and eating attitudes and behaviour were taken before and after the experimental manipulation. The manipulation was successful. After the manipulation, participants in the high personal standards condition ate fewer high calorie foods, made more attempts to restrict the overall amount of food eaten, and had significantly more regret after eating than those in the low personal standards condition. Other variables remained unchanged. It is concluded that experimental analyses can be of value in elucidating causal connections between perfectionism and eating attitudes and behaviour. © 2005 Elsevier Ltd. All rights reserved.